Integrasi Nilai-Nilai Islam dalam Kurikulum PAI - Irmawati, Irmawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of this research is to develop and evaluate an integrative PAI curriculum, which combines Islamic values ​​in depth with innovative and interactive learning methods, to prepare students well to face the modern world without sacrificing Islamic values ​​and principles. The research uses a literature study approach to analyze literature and documents related to the integration of Islamic values ​​in the PAI curriculum, with a focus on academic literature, policy documents, and electronic sources such as Google Scholar and institutional repositories. Content and comparative analysis are used to explore various approaches and practices in the implementation of Islamic values ​​in Islamic religious education, to develop a comprehensive understanding of their impact globally. The research results show that the integration of Islamic values ​​in the PAI curriculum in Indonesia faces challenges in the form of a lack of teacher authority in implementing changes, a curriculum that is too theoretical, and an inability to adapt to current developments. Research highlights the importance of a PAI curriculum that is more adaptive and responsive to social and technological needs, with a focus on developing competencies that include knowledge, skills and moral attitudes according to Islamic teachings. Efforts to improve teacher training and curriculum flexibility are expected to increase the effectiveness of PAI education in forming character and overcoming the challenges of developing times.